AN EXPERIMENT USING THE GRAPHIC VARIABLE COLOR AND THE SEE COLOR CODE ON ISARITHMIC MAPS ACCESSIBLE TO BLIND AND NORMALLY SIGHTED PEOPLE - Araújo, Niédja Sodré de; Amorim, Fabrício Rosa; Antunes, Amanda Pereira; Marchi, Sandra Regina; Schmidt, Marcio Augusto Reolon; Andrade, Andrea Faria; Delazari, Luciene Stamato (Boletim de Ciências Geodésicas, 2022)
The See Color is a color coding system based on Braille writing to communicate colors to people with visual impairments. This study assessed the perception of the theme Temperature by blind people, by using the See Color code on two isarithmic tactile maps and the perception of subjects with normal color vision. An average temperature map of Australia had 10 classes, but these intervals were regrouped into four classes on Corel Draw software. The new map was duplicated in the digital project in A4 size, both included the See Color code in two color schemes obtained from the Color Brewer website. Subsequently, they were laser-printed on swell paper to produce the tactile relief. The chromatic perception was observed, as well as the thermal sensations that the colors could represent for blind participants (06), normally sighted participants in basic education (23), and normally sighted participants in higher education (20). In this research, the See Color code showed the potential to provide spatial knowledge as a graphic language through colors in color maps for adventitiously blind and for normally sighted participants based on their perception of colors and tactile color codes.